Chimeric transcripts resulting from complex duplications in chromosome Xq28. - Zuccherato, Luciana W; Alleva, Benjamin; Whiters, Marjorie A; Carvalho, Claudia M B; Lupski, James R (Hum Genet, 2016)
Gene fusions have been observed in somatic alterations in cancer and in schizophrenia. However, the underlying mechanism(s) for their formation are poorly understood. We experimentally demonstrated the expression of splicing variants of in silico predicted chimeric genes F8/CSAG1 and BCAP31/TEX28 in two individuals with de novo complex genomic rearrangements of Xq28; F8/CSAG1 includes exonization of an ERVL-MaLR intronic repetitive element. We provide evidence that replicative repair may contribute to exon shuffling processes and diversify the repertoire of expressed transcripts.
Keywords: Antigens, Neoplasm; Base Sequence; Cell Line; Chromosomes, Human, X; Exons; Gene Duplication; Gene Expression Regulation; Gene Rearrangement; Humans; Introns; Male; Membrane Proteins; Molecular Sequence Data; Neoplasm Proteins; RNA Splicing; RNA, Messenger; Transcription, Genetic

Replicative mechanisms for CNV formation are error prone. - Carvalho, Claudia M B; Pehlivan, Davut; Ramocki, Melissa B; Fang, Ping; Alleva, Benjamin; Franco, Luis M; Belmont, John W; Hastings, P J; Lupski, James R (Nat Genet, 2013)
We investigated 67 breakpoint junctions of gene copy number gains in 31 unrelated subjects. We observed a strikingly high frequency of small deletions and insertions (29%) apparently originating from polymerase slippage events, in addition to frameshifts and point mutations in homonucleotide runs (13%), at or flanking the breakpoint junctions of complex copy number variants. These single-nucleotide variants were generated concomitantly with the de novo complex genomic rearrangement (CGR) event. Our findings implicate low-fidelity, error-prone DNA polymerase activity in synthesis associated with DNA repair mechanisms as the cause of local increase in point mutation burden associated with human CGR.
Keywords: Base Sequence; DNA Breaks; DNA Copy Number Variations; DNA Repair; DNA Replication; Frameshift Mutation; Gene Rearrangement; Genetic Variation; Genotype; Humans; Sequence Analysis, DNA; Sequence Deletion